A gestão da qualidade e o DMAIC como ferramenta de melhoria de processos: estudo de caso em uma empresa fabricante de colchões e estofados em Manaus/AM - Ferreira, Ronilson da Silva (Brasil, 2023)
Quality Management emerged as an important mechanism of competitive advantage a few decades ago and, nowadays, this importance has been increasingly evident in an economy that is increasingly diverse in terms of strategic elements and competitiveness. Within the concepts involving quality, SEIS SIGMA stands out for the effective improvement of the production line in which there are errors that cause waste. In this sense, the purpose of this work was to verify the quality and ability to improve processes in a company through the use of Six Sigma DMAIC, through an optimization project in the organization's order fulfillment capacity. The methodology of this research was exploratory and descriptive in nature, being carried out through an interview with the QMS coordinator and a study followed by improvement. The main satisfied results that the company considers quality as an element of strategy and competitiveness and within the planning of quality management takes in normative standards to always seek the best way of satisfying its customers. In addition, the improvement project presented very high results, with the current delivery rate being 26.90% higher than the delivery rate in the initial state of the process.